IMPLEMENTASI AKAD MUDHARABAH DALAM PRAKTIK PERBANKAN SYARIAH: ANALISIS TINGKAT KEPATUHAN DAN PEMAHAMAN RESPONDEN TERHADAP PRINSIP HUKUM ISLAM - fasli, nur (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This study aims to analyze the implementation of the conditions of the harm contract in Islamic banking practice and the level of compliance with the principles of Islamic law in harm. Through data, interviews, and observations, the findings show that customers and Islamic bank employees show a high commitment to compliance with the principles of Islamic law in harm transactions. Sharia bank has a systematic procedure to ensure that compliance, including performing a deep value of diligence with each customer. Even so, there is a shortage in the understanding of some customers related to the mechanism of the harm contract, and the potential for clarity in the transactions that need to be considered. The results of this study provide a positive picture of Islamic banking practices in complying with Islamic principles, but also highlighting areas that need to be repaired to increase understanding and compliance with Islamic law in financial transactions. ABSTRAK